Policing the dark web: Legal challenges in the 2015 Playpen case - Michael B. Chertoff; Eric Jardine (Centre for International Governance Innovation (CIGI), 2021)
The dark web is now a common platform for criminal activity, especially in liberal democratic regimes. The anonymity of the system gives rise to emergent use as a host of terrorist sites, gun marketplaces, drug bazaars, malicious software fora and pernicious child abuse content boards. Law enforcement can effectively police the dark web through a number of techniques, but the most technologically intensive approaches - known more euphemistically as "network investigative techniques"- raise a number of legal quandaries as their use collides with long-standing legal principles in liberal democratic regimes. Finding ways to minimize the excesses of the dark web through active law enforcement engagement, while also preserving the legal bedrock of liberal democratic societies, is key. The authors explore these issues using the Federal Bureau of Investigation's 2015 closure of the darknet Playpen child pornography site as a case study.
Keywords: 330